Implementing Village Head Election in Madura: Balancing Democratization with Traditional Violence - Ni'am, Moh. Widadun; Milasari, Milasari; Reni Prasetia Nurmawati (Journal of Indonesian Constitutional Law, 2025)
The Village Head Election (Pilkades) in Madura represents an intriguing political phenomenon, where the democratization process occurs within a strong local tradition. Although the Pilkades reflect the political participation of local communities in selecting their leaders, the reality on the ground indicates that this process is often marred by violence perpetrated by Blater.  This study aims to examine the Pilkades in Madura by highlighting aspects of democratization and the factors that provoke conflict and violence at each election stage. The study found that intense political rivalry, kinship fanaticism, and local culture are the primary catalysts for violence during the Pilkades. Conversely, more effective law enforcement efforts and conflict resolution mechanisms are essential for balancing local democracy and social stability. Using a normative legal research, this article enhances the understanding of the relationship between democratization and the culture of violence in the Pilkades in Madura. This research contributes to efforts to redesign the regulation of Pilkades in Madura by emphasising the prevention of violence in its implementation.